PREPARING AGRICULTURAL RESIDUE BASED ADSORBENTS FOR REMOVAL OF DYES FROM EFFLUENTS - A REVIEW - Kharat,D. S. (2015)
Abstract Industries engaged in dyeing operation generate coloured effluent due to the presence of spent dyes. Adsorption is among the various treatment processes employed for removal of dyes from effluents. Activated carbon is mostly used as an adsorbent in the treatment process. Attempts have been made by researchers to use non-conventional, low-cost, naturally-occurring biomass as adsorbents, including fruit peals, seeds, leaves, bark, sawdust, straw, ash, sludge and others that are abundantly available. The literature indicates that the dye adsorption capacities of these non-conventional biomasses largely depend on the methods of processing and the types of dyes. This review highlights methods used to prepare the adsorbents, along with their adsorption capacity for removal of different dyes from effluents.